Complete Genome Sequence of Veillonella nakazawae JCM 33966(T) (=CCUG 74597(T)), Isolated from the Oral Cavity of Japanese Children - Mashima, Izumi (Microbiol Resour Announc, 2021)
We report the complete genome sequence of Veillonella nakazawae JCM 33966(T) (=CCUG 74597(T)). This bacterium is a member of the oral Veillonella and has the potential to be anticariogenic as an oral probiotic seed.